Fish Anisakidae Helminthes in KHuzestan Province, South West of Iran - A Farahnak; 1I Mobedi; R Tabibi (Tehran University of Medical Sciences, 2002)
Fish including; Barbus spp, Cyprinus carpio, Liza abu and Aspius vorax have very important role in the economic condition of the rural areas of Khuzestan province. These fish have been consumed as fried or roasted. Inadequately cooked fish, could be served as a source of infection in these communities. For this reasons, 701 fish were trapped from 4 lagoons (Atash, Sobhanieh, Al-hai, Houfel) and transported alive to Ahwaz Health Research Center .Their skin, gills, eyes, muscles, intestine and body cavity were examined carefully. In 54 (7.7%) of fish,.6 cases of Contracaecum sp. (0.85%) and 48 Anisakis sp. (6.8%) were identified belong to helminth family of anisakidae. These results suggested that human anisakiasis could be health hazard in these areas.